Lipoma-induced jejunojejunal intussusception: a novel “bow-tie sign” - Jain, Ankit; Verma, Neha; Kamra, Aman; Malhotra, A. K.; Bhutani, Sumit; Mittal, Yamini; Mittal, Vinamra (International Journal of Research in Medical Sciences, 2025)
Intussusception, a condition predominantly observed in infants and young children, is one of the leading causes of acute abdominal emergencies, second only to appendicitis. In contrast, adult intussusception is rare, accounting for less than 5% of all cases and 1% to 5% of bowel obstructions. While pediatric intussusception is often idiopathic, over 90% of adult cases have an identifiable organic cause, including malignancy. Among benign causes, small bowel lipomas are a rare but significant lead point for intussusception. We report a case of jejunojejunal intussusception in an adult patient caused by a small bowel lipoma, which presents with a novel intraoperative finding we describe as the "bow-tie sign." This case emphasizes the importance of imaging and appropriate surgical management.